SOME ASPECTS OF INTEGRATION IN EDUCATION BETWEEN KAZAKHSTAN AND CHINA - Цзуньминь, У; Акрамова, Алия; Лицзюнь, Лю (Pedagogy and Psychology, 2022)
In the modern world, there is a conceptualization of the competition of great powers in the field of state educational policy. Kazakhstan and the People’s Republic of China are advanced and strong countries in the region of Central and South Asia. The geoeconomic, social and cultural policies of the two countries have an impact on the development of not only the countries of this region, but also on political and economic events around the world. In the context of globalization, the Republic of Kazakhstan and the PRC realize the need to change international relations and cooperation in the field of science and education. Strengthening cooperation in the field of education, which contributes to the development and implementation of innovations in education, the development of relations between the two countries, remains one of the main tasks of China-Kazakhstan relations. Numerous agreements on the coordination of macroeconomic policy and cooperation in the field of education are the basis of the integration process between China and Kazakhstan. The Confucius Institute, as a network of international cultural and educational centers, and the Shanghai Cooperation Organization have become a major platform for education and cultural exchanges between the two countries. The authors of this article made an attempt to reveal the process of integrating knowledge into the global scientific space, since cooperation in the field of education contributes to the increase of the competitiveness of the education system and the approximation to the best international practices.